2008
DOI: 10.1021/ja8056908
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of β-Hydrogen Elimination from Organoplatinum(II) Enolate Complexes

Abstract: A detailed mechanistic investigation of the thermal reactions of a series of bisphosphine alkylplatinum(II) enolate complexes is reported. The reactions of methylplatinum enolate complexes in the presence of added phosphine form methane and either free or coordinated enone, depending on the steric properties of the enone. Kinetic studies were conducted to determine the relationship between the rates and mechanism of β-hydrogen elimination from enolate complexes and the rates and mechanism of β-hydrogen elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 35 publications
(75 reference statements)
1
28
0
Order By: Relevance
“…C-O reductive elimination from the d 6 metal center usually occurs through an S N 2 route and a direct C-O elimination pathway. 31 Groves reported a facile C-O reductive elimination from b-hydroxyalkyl complexes of rhodium tetraphenyl porphyrin in KOtBu/C 6 D 6 by a proposed S N 2 pathway. 19 The origin of the selective formation of ketone in water and epoxide in KOH/DMSO may be that the nucleophilicity of the alkoxy group is dramatically reduced in water due to the solvation.…”
Section: Formation Of Epoxides From B-hydroxyalkyl Rhodium Porphyrin ...mentioning
confidence: 99%
“…C-O reductive elimination from the d 6 metal center usually occurs through an S N 2 route and a direct C-O elimination pathway. 31 Groves reported a facile C-O reductive elimination from b-hydroxyalkyl complexes of rhodium tetraphenyl porphyrin in KOtBu/C 6 D 6 by a proposed S N 2 pathway. 19 The origin of the selective formation of ketone in water and epoxide in KOH/DMSO may be that the nucleophilicity of the alkoxy group is dramatically reduced in water due to the solvation.…”
Section: Formation Of Epoxides From B-hydroxyalkyl Rhodium Porphyrin ...mentioning
confidence: 99%
“…β-H elimination could occur via a five-coordinate intermediate, 3234 although, in coordinatively saturated systems it has been proposed to occur via alkoxide dissociation 3537 or in bimolecular fashion. 38,39 Given the strain of the chelates in complex 4 , phosphine dissociation may also be possible, 32,33,40,41 opening up a cis coordination site for β-H elimination. 4244 Further studies are necessary to determine the mechanism in the present system.…”
mentioning
confidence: 99%
“…After ligand substitution (Scheme 3), palladium enolate III may follow two pathways: 1) reductive elimination to give a-arylated product 3 a, or 2) bÀH elimination to give olefin complex IVa. [24] Bond rotation provides isomeric complex IVb, which can undergo olefin insertion either into the Pd À H or the Pd À Ar bonds. Previous calculations with PCy 3 as the ligand indicated that the former insertion is much-more-kinetically favored than the latter.…”
mentioning
confidence: 99%